Perception of Hypertension Patients on Treatment in Tamiang Layang Hospital, Central Kalimantan, Indonesia - Theresia Jamini; Putri Perdana Anggreni; Dwi Marta Agustina (Jurnal Surya Medika (JSM), 2021)
Hypertension is a significant health problem considering the complications it causes. The research objective was to describe hypertensive patients' perceptions of their treatment at the inpatient installation of RSUD Tamiang Layang in 2019. Quantitative research methods with descriptive research design were applied with sampling with non-probability sampling is purposive sampling, amounting to 30 respondents—the process of collecting data using a questionnaire instrument. The data obtained were then processed and analyzed using Univariate Analysis. The results showed that 93.33% of respondents had a positive perception classification of their treatment, and as many as 6.67% of respondents had a negative perception classification. It was concluded that hypertensive patients' perception towards treatment in the inpatient room at RSUD Tamiang Layang in 2019 has a positive classification of treatment, which means that most patients know and understand hypertension treatment both pharmacologically and non-pharmacologically, although it is still not optimal.